Tingimento de seda e lã com corante natural extraído de cascas de cebola - Silva, Andreia Bortoluzzi da (2013)
Allium cepa, commonly called onion, is used worldwide for culinary purposes. It has a strong flavor besides characteristic pungent odor. The bulb comprises layers of fleshy modified leaves, surrounded by outer layers. This plant has an array of varieties available in the market which makes possible its use as dye fabrics with successful results. Nowadays, dyeing with natural dyes is again gaining strength in order to generate a less polluting and biodegradable effluent, besides being renewable and harmless to human health. Because of the great difficulty on color reproduction and standardization of dyes, natural dyes have a very empirical process, with few investigation of the sorption mechanism. In the present work, silk and wool fabrics were dyed with the dye extracted from the peels of onions (Allium cepa). Dyeing mechanism was investigated through evaluation of the influence of the initial dye concentration, pH and temperature. The influence of the potassium alum mordant in the wash fastness of dyed fabrics was also studied. It was found that the initial dye concentration 10 g L-1, pH 3 and temperatures of 80 and 90 °C are the conditions which produced the best adsorption results in the dyeing process for wool and silk, respectively. These results were used to investigate the kinetics and equilibrium of the dyeing process, through adsorption isotherms. The pseudo-second order equation best represents the kinetic mechanism for dyeing both fabrics, which is related to chemisorption process. Equilibrium data was easily adjusted to the Langmuir-Freundlich model, indicating a significant contribution of the chemisorption process on a monolayer. It was also observed that the Allium cepa dye was better retained in the wool fabric. The thermodynamic properties, Gibbs free energy (ΔG°), enthalpy (ΔH°) and entropy (ΔS°) were also evaluated taking into account equilibrium data at 70, 80 and 90 °C. Adsorption of the Allium cepa dye in silk dyeing is a spontaneous and endothermic process, while in wool it is spontaneous as well but endothermic from 70-80 °C and exothermic at 80-90 °C.